Beobachtungen zur Turfan-Chandoviciti - Chen, Ruixuan (Indo-Iranian journal, 2013)
In 1958, a number of birchbark fragments in the Berlin collection of Turfan manuscripts were edited and published by Dieter Schlingloff under the title of Chandoviciti. He ascribed them to three independent texts on Sanskrit metrics, which contained numerous exemplary verses of a wide variety of Sanskrit meters. Therefore some scholars felt justified in assuming that the texts dated by Schlingloff in the second half of the fourth century ce were originally a collection of exemplary verses. Nevertheless the textual history of those texts remains obscure. This recent research is based on a scrutiny of the original source, while bringing about a correction of several readings. Furthermore, some palaeographical remarks might be able to suggest a somewhat later dating of the manuscripts in question than that proposed by Schlingloff. With regard to the title of this treatise, it follows from a historical perspective that Chandoviciti per se as a title would hardly be probable, if not impossible. In the last part of this article, light is shed on the internal diversity and inconsistency among those exemplary verses, which render it plausible that the so-called Turfan-Chandoviciti could have been a „mixed“ booklet compiled from at least four different sources which was then continuously abridged over the course of time from the very beginning of its spread along the Silk Road up to its final entry into Xinjiang.